I wish, I wish - Shipton, Paul (Oxford Oxford University Press, 2014)
Have you ever wanted a way to make all your dreams come true? In I Wish, I Wish Debbie buys an old lamp for her mother, a modern-day genie appears out of it - but will the genie be quite what Debbie expects? TreeTops Fiction contains engaging novels from top authors and illustrators with the variety children need to develop a love of reading!
Include Illustrations
Keywords: Magic -- Wishes -- Welsh language